A PSYCHOLOGICAL REVIEW OF SHARIA ECONOMIC IMAGOLOGY IN THE NARRATIVES OF ULAMA FIGURES IN CHILDREN’S STORIES - Tristan Rokhmawan; Lailatul Fitriyah (Journal of Language and Literature Education, 2025)
This article presents a psychological review of Sharia economic imagology in the narratives of ulama figures in children’s stories. The study aims to examine how children’s stories centered on ulama figures are constructed as media for Sharia economic education that align with the characteristics of early childhood psychological development. Employing a qualitative approach, this study applies content analysis to three illustrated children’s storybooks containing Sharia economic values. The analysis focuses on character representation, narrative structure, symbolic elements, and psychological mechanisms that support knowledge construction and the presentation of behavioral exemplars for children. The findings indicate that Sharia economic values in the stories are conveyed in concrete, contextual, and narrative forms through emotionally safe ulama figures. Children’s economic understanding is built through psychological mechanisms such as observational learning, positive emotional reinforcement, simple narrative cause–effect patterns, and behavioral habituation through repeated routines. Furthermore, the study identifies variations in psychological approaches, including reflective emotional experiences, social and relational awareness, and consistent role modeling. These findings confirm that ulama-centered narratives function as effective psychological media for Sharia economic education in children’s literature.